1973
DOI: 10.2307/3311135
|View full text |Cite
|
Sign up to set email alerts
|

Schools as Sorters: The Constitutional and Policy Implications of Student Classification

Abstract: During the past two decades, courts have sought to define with particularity the meaning (or, better, meanings) of equal educational opportunity. Only recently, however, have courts examined withinschool practices-ability grouping, special education placement, exclusion of "ineducable" children-which classify students on the basis of academic performance or potential. In this Article, Professor Kirp assesses both the plausibility of treating student classification issues in equal protection and due process ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

1975
1975
1986
1986

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…Yet one such observor who has an outstanding track record of speaking out on matters of educational equity is not bothered by this development (Kirp, 1973;Kirp, Buss, & Kuriloff, 1974). …”
Section: Analysis Of This Shift From Judicial To Legislative Arenamentioning
confidence: 96%
“…Yet one such observor who has an outstanding track record of speaking out on matters of educational equity is not bothered by this development (Kirp, 1973;Kirp, Buss, & Kuriloff, 1974). …”
Section: Analysis Of This Shift From Judicial To Legislative Arenamentioning
confidence: 96%
“…The court held that lack of intent did not exonerate the school system. As has been pointed out in several analyses of this case (Kirp, 1973;Shea, 1977), the court confused the issues of achievement and innate learning ability when it stated that the purpose of the track system was to classify students according to their innate ability to learn, and concluded that it could only be legitimately maintained if it accurately reflected these innate abilities.…”
Section: School Classification or Ability Groupingmentioning
confidence: 98%
“…In large city school systems, less than 10 percent ever return to regular classrooms. Kirp (1973) argues that given the stigma attached to such assignment, court suits challenging assignment to special education classes should reverse procedural burden such that the school officials are required to show that the special education program accomplishes what it is supposed to do: that it sufficiently benefits students to justify the inevitable stigma attached to such placement.…”
Section: School Classification or Ability Groupingmentioning
confidence: 99%
“…This is clearly a questionable conclusion, and a good deal of evidence suggests that it is false (see especially, Bowles and Gintis, 1976:102-148;Kirp, 1973;Thurow, 1972). This is clearly a questionable conclusion, and a good deal of evidence suggests that it is false (see especially, Bowles and Gintis, 1976:102-148;Kirp, 1973;Thurow, 1972).…”
Section: Implications For the Chicano Communitymentioning
confidence: 99%